Stimulation of amino acid transport in Saccharomyces cerevisiae by metabolic inhibitors - Horák, J; Kotyk, A; Ríhová, L (Folia microbiologica, 1978)
Inhibitors of energy metabolism (3-chlorophenylhydrazonomalononitrile, antimycin A, iodoacetamide, dicyclohexylcarbodiimide) but not of transport (uranyl ions) stimulate at low concentrations the uptake of L-leucine, L-glutamic acid, L-arginine and, to a lesser degree, of 2-aminoisobutyric acid in Saccharomyces cerevisiae. The effect is apparent only after augmenting the energy reserves of cells by preincubation with D-glucose or, more strikingly, with ethanol. It is absent in a mutant (op1) lacking the translocation system for ADP--ATP in mitochondria. The presence of two different energy reserves for amino acid transport is indicated (one in energy-poor, the other in energy-rich cells). The stimulating effect appears to be caused by a retarded degradation of the transport proteins as occurs at a lowered level of mitochondria-produced ATP.
Keywords: Kinetics; aktivní transport; Carbonyl Cyanide m-Chlorophenyl Hydrazone; antimycin A; Dicyclohexylcarbodiimide; Saccharomyces cerevisiae; Iodoacetamide; adenosintrifosfát; dicyklohexylkarbodiimid; Leucine; Adenosine Triphosphate; leucin; Biological Transport, Active; Antimycin A; karbonylkyanid-m-chlorfenylhydrazon; jodacetamid; Uranium; Amino Acids; aminokyseliny; kinetika; uran